Avaliação técnica e econômica da extração de madeira com forwarder em diferentes volumes por árvore e comprimentos de toras - Martins dos Santos, Sérgio Luis; Cardoso Machado, Carlos (Instituto de Ecología, A.C., 2016)
The objective of the present work is to analyze technical and economical forwarder operations in function of the tree volume and different log length (2,8 m; 4,0 m and 5,5 m). It was observed that the forwarder productivity increased directly proportional to the increase of the tree volume and to the log length. The production costs, for your time, had an inverse behavior to the productivity.